Suriname. Significant achievements 2015 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Suriname during 2015 are identified, with respect to the needs and interests of the country, strengthening issues such as ecotourism, technology, composting, use of greenhouses, irrigation systems, water management, good agricultural practices , risk mitigation, hospitality, nursery employment and resilience against climate change. Likewise, work was done in a museum, the use of biofuels, in the use of organic fertilizers, the inclusion of excluded groups, such as women, in matters of legalization and registration. Finally, it supported the recovery of the soil, the cultivation of tissues and the improvement of value chains such as onions, pineapples and cattle.